PENGARUH MODEL PEMBELAJARAN ADVANCE ORGANIZER TERHADAP KETERAMPILAN MEMBACA CERPEN SISWA DI SMA - Puspita Loka, Vilda; Hidayatullah, Syarif (SASTRANESIA: Jurnal Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to determine the effect of the advance organizer learning model on students' short story reading skills at SMA. To find out this result, the Pre-experimental method was used with a Quasi Experimental Design research design. The sampling technique used is Simple Random Sampling. The research subjects used were 31 students. Based on the test results on the control and experimental classes, a t-test was produced with the results tcount = 2.039 < ttable = 2.038.99 in the control class; tcount = 2.671 > ttable = 1.8065 in the experimental class with a significant level of = 0.05 and the number of samples is 31 students. Based on this research, there is an influence of the Advance Organizer Model on the ability to read short stories at SMA which has an influence on student learning.